The Rationality Behind the Choice of Kupang City Residents to Become Online Motorcycle Taxi Drivers - Muhammad Usman, Syaiful; Ahmad, Abidin; Purnamasari, Hasanah; Salem, Muh. Amiruddin; Sulisworo, Dwi (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2024)
This research aimed to explore the rationality behind the choice of Kupang City residents to become online motorcycle taxi drivers, investigating their management of work time and conducting interviews with relevant informants. Qualitative research methods were employed, utilizing a descriptive research design to examine natural phenomena, with the researcher serving as the primary instrument. Data collection involved observation, interviews, and documentation. The findings revealed several key points: Firstly, there was minimal competition in 2018, coinciding with the rise of Grab's popularity in Kupang City. Secondly, the flexibility of working hours was highlighted, allowing drivers to operate at their convenience, day or night. Thirdly, income emerged as a significant factor, contributing to meeting the drivers' financial needs. It was observed that online motorcycle taxi drivers come from diverse backgrounds, including lecturers and office employees, with some relying on this work as their primary source of income while others consider it a supplementary endeavor.